PENGUATAN SISTEM PENDIDIKAN DALAM ROADMAP PENGEMBANGAN SDM MENUJU INDONESIA EMAS 2045: SYSTEMATIC LITERATURE REVIEW - Eka Aprilianty (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze the urgency of human resource (HR) development in supporting the realization of Indonesia Emas 2045, to formulate a strategic roadmap, to compare international best practices (Finland, Japan, and Australia), and to develop contextual cross-sector policy recommendations. This research employs a Systematic Literature Review (SLR) method based on PRISMA guidelines. Data were collected from reputable academic databases such as Scopus, Google Scholar, SINTA, and institutional reports, covering publications from 2020–2026. From an initial pool of relevant studies, 20 articles met the inclusion criteria and were analyzed comprehensively. The findings indicate that HR development in Indonesia must be carried out in an integrated and sustainable manner across eight key sectors: education, employment, research and innovation, health, economic transformation, social inclusion, population management, and digitalization. Furthermore, successful implementation requires strong institutional governance, cross-sector collaboration through a triple helix model (government–industry–academia), increased investment in research and development, and competency-based education reform. This study concludes that without high-quality human resources, Indonesia’s demographic bonus may become a burden. However, with an adaptive, inclusive, and evidence-based roadmap, Indonesia has a significant opportunity to achieve its vision of becoming a developed nation by 2045. ABSTRAK Penelitian ini bertujuan untuk menganalisis urgensi pengembangan sumber daya manusia (SDM) dalam mendukung pencapaian Indonesia Emas 2045, merumuskan kerangka peta jalan strategis, mengkaji praktik terbaik internasional, serta menyusun rekomendasi kebijakan lintas sektor yang berkelanjutan. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan mengacu pada pedoman PRISMA. Data diperoleh dari basis data ilmiah seperti Scopus, Google Scholar, dan SINTA, serta laporan lembaga internasional, dengan rentang publikasi tahun 2020–2026. Dari hasil identifikasi literatur, sebanyak 20 artikel yang memenuhi kriteria inklusi dianalisis secara mendalam. Hasil kajian menunjukkan bahwa pengembangan SDM Indonesia perlu dilakukan secara terintegrasi melalui delapan sektor utama, yaitu pendidikan, ketenagakerjaan, riset dan inovasi, kesehatan, ekonomi, sosial inklusif, kependudukan, dan digitalisasi. Praktik terbaik dari beberapa negara maju menekankan pentingnya pendidikan berbasis kompetensi, penguatan sistem vokasi, serta pengembangan ekosistem inovasi yang terhubung dengan industri. Implementasi strategi tersebut memerlukan dukungan kelembagaan yang kuat, kolaborasi triple helix, serta peningkatan investasi pada sektor pendidikan dan riset. Kesimpulannya, pengembangan SDM menjadi faktor kunci dalam memanfaatkan bonus demografi menuju Indonesia Emas 2045. Tanpa strategi yang terarah, bonus demografi berisiko menjadi beban pembangunan. Sebaliknya, dengan roadmap yang adaptif dan inklusif, Indonesia berpeluang menjadi negara maju pada tahun 2045.